Case Report: Recurrent pericardial tamponade in a child with COVID-19 - Győri, Ádám; Decsi, Tamás; Stankovics, József; Nyul, Zoltán; Környei, Mária; Masszi, György; Leibinger, Evelin; Mosdósi, Bernadett (Frontiers in Pediatrics, 2022)
Background. Pericarditis is rare in Coronavirus disease 2019 (Covid-19) infection and only a few cases were reported in children. Case presentation. We present the case of a 15-year-old boy with symptoms of high fever and worsening chest pain during COVID-19 infection. We report a 15-year-old Covid-19 positive patient presented with high fever and worsening chest pain. Chest computer tomography (CT) and echocardiography confirmed verified the diagnosis of pericardial tamponade requiring urgent immediate drainage. Despite In spite of antiviral drug treatment, after 18 days later another severe attack developed requiring repeated pericardiocentesis and required pericardial drainage again. High dose ibuprofen, colchicin and the interleukin-1 antagonist, anakinra were given. The Clinical symptoms and laboratory parameters improved after seven days of treatment. Autoinflammatory diseases were also suspected in the background behind the severe pericarditis, but genetic analysis ruled out any mutations. Conclusion. Pericarditis associated with COVID-19 infection may present in the acute phase or later as MIS-C. Though pericardial tamponade related to ongoing Covid-19 infection is rare in children, even biological treatment with interleukin-1 antagonist may be needed might be necessary to control the inflammation.